NEW DRUG FORMULATIONS FOR ACNE VULGARIS – PATHOGENESIS BASED TREATMENT OF ACNE VULGARIS - Sukmawati Tansil Tan; Yohanes Firmansyah (Jurnal Medika Hutama, 2021)
Acne vulgaris is an inflammatory condition that affects the pilosebaceous glands on a localized basis. According to the Indonesian Cosmetics Dermatology Study, the prevalence of acne vulgaris increased between 2006 and 2009. Young women between the ages of 14-17 years have a prevalence of 83-85 percent, while men between the ages of 16-19 years have a prevalence of 95-100 percent. Acne vulgaris has a significant physical and psychological impact on adolescent sufferers. Accuracy in the treatment of acne vulgaris is critical because it has an impact on the patient's recovery and prognosis. A topical anti-acne cream containing retinoids, antibiotics, and corticosteroids is one of the best options because it contains all of the components necessary to treat acne. The purpose of this study was to ascertain the proportion of acne vulgaris sufferers in adolescents aged 14-19 years with mild, moderate, and severe acne levels prior to and following intervention, to ascertain the relationship between intervention and reduction in the severity of acne vulgaris, and to ascertain the proportion of acne vulgaris sufferers in adolescents who received intervention and experienced a reduction in the severity of acne vulgaris. This study is a retrospective cohort study conducted at the Indra Clinic. The sample of this study was the entire group of adolescents aged 14-19 years with acne vulgaris who came to the study site in the 2016-2017 period and met the inclusion criteria. The formulation observed was a combination of anti-acne cream with the active ingredient clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%, with the comparative drug being a standard regimen containing 0.05% tretinoin. The dependent variables in this study were treatment success (improved or not) after 4 weeks intervention, side effects during treatment, and post-treatment symptoms. The results indicated the cure rate was 87,6 percent for the 97 respondents who received a combination formulation containing Clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%, compared to a 71,0 percent cure rate for the 93 respondents who received standard therapy containing Tretinoin 0.05% (p-value : 0,008).